2019
DOI: 10.3892/mmr.2019.10087
|View full text |Cite
|
Sign up to set email alerts
|

Sanguinarine induces apoptosis of human lens epithelial cells by increasing reactive oxygen species via the MAPK signaling pathway

Abstract: Posterior capsular opacification (PCO) remains a major complication of cataract surgery and is the most common reason for loss of vision. PCO is primarily associated with uncontrolled proliferation of residual human lens epithelial cells (HLEs). Sanguinarine is a type of benzophenanthridine alkaloid extracted from the herbaceous plant Sanguinaria canadensis , which is widely used for its anti-microbial, anti-inflammatory, anti-oxidative and anti-proliferative properties. However, studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
2
7
0
Order By: Relevance
“…AKT signaling pathway is crucial in promoting endothelial cell survival while ERK1/2 and p38 (Tyr182) are vital in proliferation and migration respectively ( Basini et al, 2007c ; Cheng et al, 2017 ). This result was in line with several previous studies that SC demonstrated antiangiogenic and anti-invasive effect ( Cheng et al, 2017 ; Zhang and Huang, 2019 ). However, our result was different from the previous study ( Eun and Koh, 2004 ), which reported that Sanguinarine suppressed VEGF-induced Akt phosphorylation but not ERK 1/2 or PLCr1 phosphorylation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…AKT signaling pathway is crucial in promoting endothelial cell survival while ERK1/2 and p38 (Tyr182) are vital in proliferation and migration respectively ( Basini et al, 2007c ; Cheng et al, 2017 ). This result was in line with several previous studies that SC demonstrated antiangiogenic and anti-invasive effect ( Cheng et al, 2017 ; Zhang and Huang, 2019 ). However, our result was different from the previous study ( Eun and Koh, 2004 ), which reported that Sanguinarine suppressed VEGF-induced Akt phosphorylation but not ERK 1/2 or PLCr1 phosphorylation.…”
Section: Discussionsupporting
confidence: 93%
“…Vascular Endthelial Growth Factor-Induced Phosphorylation of Anti-Phospho-Protein Kinase B, p38-MAPK and Extracellular Signal-Regulated Kinase 1/2 AKT, p38-MAPK, and ERK1/2 are crucial factors triggered by VEGF to induce the angiogenesis process, including survival, migration and proliferation of endothelial cells (Aiello et al, 1995;Roh et al, 2016;Cheng et al, 2017;Zhang and Huang, 2019). Thus we investigated the effect of SC on VEGF-induced phosphorylation of AKT (p-AKT), p38-MAPK (p-p38-MAPK), and ERK1/2 (p-ERK1/2) using HRMECs ( Figure 7A).…”
Section: Sanguinarine Chloride Suppressedmentioning
confidence: 99%
“…40,41 Moreover, cataracts are directly related to the apoptosis of LECs caused by oxygen free radicals. 42,43 It has been reported that antioxidant genes and drugs can inhibit the oxidative damage caused by H 2 O 2 by reducing the activity of ROS. 44,45 Lens epithelial cells initiate apoptosis-related signal transduction pathways under oxidative stress, which mediates the apoptosis of LECs and promote the development of cataracts.…”
Section: Discussionmentioning
confidence: 99%
“…The p38 mitogen activated protein kinase (MAPK) signaling pathway, activated by oxidase stress, cytokines, and growth factors, plays a crucial role in controlling growth, apoptosis, and differentiation (Cuadrado and Nebreda, 2010). Multiple factors have been shown to affect oxidative stress and cell apoptosis via the p38 MAPK signaling pathway in HLECs and cataract tissues (Zhou and Menko, 2004;Huang et al, 2014;Bai et al, 2015;Ji et al, 2016;Gong et al, 2018;Zhang and Huang, 2019). We have previously reported that CRTAC1 knockdown significantly attenuated UVB-induced apoptosis and decreased p38 phosphorylation in HLECs ( Ji et al, 2016).…”
Section: Figmentioning
confidence: 99%